2020
DOI: 10.1038/s41598-020-70709-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphate levels modify the impact of parathyroid hormone levels on renal outcomes in kidney transplant recipients

Abstract: Separate assessment of mineral bone disorder (MBD) parameters including calcium, phosphate, parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23), 25-hydroxyvitamin D, and 1,25-dihydroxyvitamin D (1,25D) predict renal outcomes in kidney transplant recipients (KTRs), with conflicting results. To date, data simultaneously evaluating these parameters and interwoven relations on renal outcomes are scarce. We conducted a prospective long-term follow-up cohort study included 263 KTRs with grafts functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Only one published study investigated the association between iFGF23 and the overall graft loss in KTRs so far [ 21 ]. In line with our study, the positive association of iFGF23 with poor outcome in the unadjusted analysis was no longer significant after adjusted for risk factors in the multivariate analysis ( P = 0.97), however, this study did not analyze cFGF23.…”
Section: Discussionmentioning
confidence: 99%
“…Only one published study investigated the association between iFGF23 and the overall graft loss in KTRs so far [ 21 ]. In line with our study, the positive association of iFGF23 with poor outcome in the unadjusted analysis was no longer significant after adjusted for risk factors in the multivariate analysis ( P = 0.97), however, this study did not analyze cFGF23.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, cholecalciferol supplementation can be a promising strategy to reduce PTH levels among KTRs without increasing serum calcium levels. Considering the relationship between high PTH levels and worse outcomes, including incident fracture, graft survival, and all‐cause mortality among KTRs, ( 28 , 29 , 30 ) further studies are required to determine whether vitamin D supplementation provides benefits on long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that low levels of 25-OH-VitD might be associated with worse graft outcomes, thus, promoting rejection episodes, possibly through the immunomodulatory mechanism exerted on the immune system (30). In any case, the direct and independent effect of 25-OH-VitD on graft outcome is still a matter of debate (26,(31)(32)(33).…”
Section: Vitamin Dmentioning
confidence: 99%